Surface-hopping trajectories for OH(A(2)Σ(+)) + Kr: Extension to the 1A″ state - Perkins, T; Herráez-Aguilar, D; McCrudden, G; Kłos, J; Aoiz, F; Brouard, M (American Institute of Physics, 2015)
We present a new trajectory surface hopping study of the rotational energy transfer and collisional quenching of electronically excited OH(A) radicals by Kr. The trajectory surface hopping calculations include both electronic coupling between the excited 2(2)A' and ground 1(2)A' electronic states, as well as Renner-Teller and Coriolis roto-electronic couplings between the 1(2)A' and 1(2)A″, and the 2(2)A' and 1(2)A″ electronic states, respectively. The new calculations are shown to lead to a noticeable improvement in the agreement between theory and experiment in this system, particularly with respect to the OH(X) rotational and Λ-doublet quantum state populations, compared with a simpler two-state treatment, which only included the electronic coupling between the 2(2)A' and 1(2)A' states. Discrepancies between the predictions of theory and experiment do however remain, and could arise either due to errors in the potential energy surfaces and couplings employed, or due to the limitations in the classical treatment of non-adiabatic effects.